2022
DOI: 10.1007/s11136-022-03124-z
|View full text |Cite|
|
Sign up to set email alerts
|

Neurocognitive functioning and health-related quality of life of children after pediatric intensive care admission: a systematic review

Abstract: Objective This study systematically reviewed recent findings on neurocognitive functioning and health-related quality of life (HRQoL) of children after pediatric intensive care unit admission (PICU). Data sources Electronic databases searched included Embase, Medline Ovid, Web of Science, Cochrane CENTRAL, and Google Scholar. The search was limited to studies published in the last five years (2015–2019). Study selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 97 publications
0
8
2
Order By: Relevance
“…In this study, the objectively tested general intelligence and verbal memory outcomes in children with MIS-C were comparable with the Dutch normative data. Interestingly, these age-adequate full scale intelligence scores in children with MIS-C contrast with the lower intelligence scores reported in recent meta-analyses in the general PICU population (14)(15)(16). We also found that the parent-reported executive function scores (BRIEF questionnaire) were comparable with the general Dutch population, which, again, contrasts with the previously reported worse parent-reported executive functions in the general PICU population ( 17).…”
Section: Neurocognitive Outcomescontrasting
confidence: 91%
See 2 more Smart Citations
“…In this study, the objectively tested general intelligence and verbal memory outcomes in children with MIS-C were comparable with the Dutch normative data. Interestingly, these age-adequate full scale intelligence scores in children with MIS-C contrast with the lower intelligence scores reported in recent meta-analyses in the general PICU population (14)(15)(16). We also found that the parent-reported executive function scores (BRIEF questionnaire) were comparable with the general Dutch population, which, again, contrasts with the previously reported worse parent-reported executive functions in the general PICU population ( 17).…”
Section: Neurocognitive Outcomescontrasting
confidence: 91%
“…An explanation for the current MIS-C cohort with better overall cognitive function might be the short length of stay in the PICU during acute illness. In the general PICU population, prolonged length of stay on the PICU is associated with worse cognitive functioning ( 14 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children surviving PICU often experience a constellation of post-PICU long-term cognitive, psychological, and physical impairments, commonly referred to as post-intensive care syndrome—pediatric (PICS-p) (1–3). Pediatric survivors of critical care are at risk for cognitive impairments and psychological problems that negatively impact their daily functioning and quality of life (4–10). Risk factors and mechanisms underlying neurocognitive and psychological outcomes are not yet well understood but may be related to delirium, mechanical ventilation, sepsis, sedation/analgesic medications, length of ICU admission, severity of illness, severe respiratory failure/hypoxia, and inflammation (11–14).…”
mentioning
confidence: 99%
“…Although still emerging, the literature indicating cognitive impairments following pediatric critical illness is growing (5–7, 10, 14–16). Various risk factors have been associated with acquiring functional or cognitive impairments following a PICU admission, including a trauma, oncologic or neurologic diagnosis, longer length of PICU stay, higher risk of mortality, invasive mechanical ventilation, renal replacement therapy, cardiopulmonary resuscitation, and extracorporeal membrane oxygenation (13, 17).…”
mentioning
confidence: 99%